The Role of Calcium-Based Additives in Bentonite Stabilization: A Comparative Evaluation - Alibrahim, Bashar; Garoushi, Ali Hossien Basheer; Uygar, Eris (Springer Heidelberg, 2025)
Waste recycling plays a critical role in addressing environmental challenges by conserving natural resources, reducing pollution, and mitigating the environmental impact of human activities. However, bentonite has been known to exhibit a propensity for swelling and shrinking in response to changes in moisture content, which can result in severe cracks. This study aims to examine the effects of various recycled calcium-based additives on the stabilization of bentonite, including calcium carbonate, calcium phosphate, calcium sulfate, and calcium hydroxide. The results of the tests conducted reveal that calcium hydroxide proves to be the most effective in enhancing the compressibility, shear strength, and cracking resistance of the bentonite barrier, while also significantly reducing its tendency to swell and shrink.
Keywords: Bentonite; Calcium-based additives; Marble dust; Soil crack analysis; Swell-shrink behavior